Enhanced hydrogen evolution by rGO decorated copper nickel tin sulphide (CNTS-rGO) in acidic medium by water splitting. (19th July 2022) - Sheebha, I.; Maheskumar, Velusamy; Sebastian, Anju; Vidhya, B.; Sakunthala, A.
Abstract: A simple hydrothermal synthesis approach for rGO decorated copper nickel tin sulfide (CNTS-rGO) micro flowers is devised in this research. Due to the depletion of fossil resources in the environment, the demand for energy has recently increased tremendously. Here we report the preparation of CNTS with various concentration of GO (Graphene Oxide) (10–50 mg). The prepared material is characterized for its structural and optical properties using XRD, FESEM, XPS, HRTEM, Raman studies and UV-DRS respectively. Surprisingly, graphene oxide incorporated CNTS material demonstrates an initial overpotential due to the abundance of active sites. Due to their unique properties, they prove to be intriguing and promising alternative catalysts. A minimal start overpotential of −235mV, a low Tafel slope of 57 mV dec −1 and outstanding long-term stability is found among one of the concentrations of rGO. This is the finest HER performance in acidic medium on electrochemical studies for CNTS-rGO. Graphical abstract: Image 1 Highlights: Incorporating reduced graphene oxide in hierarchical flower like CNTS. CNTS-rGO (10-50) is explored for hydrogen energy evolution reaction. Increased electrocatalytic activity considerably by incorporating rGO in CNTS. High current density of 140.8 mAcm −2 for the enhanced hydrogen evolution reaction.